Enhancing Restaurant Profits via Strategic Wine Sales - Scott Sheridan; Marc Dressler (Businesses, 2025)
The restaurant industry, especially fine dining, is characterized by intense competition and an increasing number of closures. Wine is a profit lever, but the exploitation of sales potential can present a challenge. As consumers encounter more extensive wine lists, they often find themselves overwhelmed. A restaurant experiment in Stuttgart, Germany, examined strategies to simplify decision-making for customers and their impact on wine purchases and the dining experience. This experiment, conducted at a small fine-dining establishment, aimed to understand how wine descriptions and pairing recommendations influence customer choices and behavior, revealing key insights that wineries and restaurants can leverage to boost wine sales. The findings underscore the power of wine descriptions and strategic pairing recommendations in enhancing customer engagement. They suggest that restaurants can increase their wine sales by integrating well-crafted wine descriptions into menus, while wineries can benefit by providing comprehensive tasting notes and pairing suggestions that align with restaurant offerings. For both sectors, understanding the sensory and psychological factors that shape wine appreciation can offer a competitive edge.